Yield of maize and cowpea in an alley cropping system in relation to available light - Lawson, T.L.; Kang, B.T. (Elsevier, 1990)
Measurements of incident solar radiation were made in sequentially cropped maize (Zea mays L.) and cowpea (Vigna unguiculata L. Walp.) planted between hedgerows of shrubs in an alley cropping pattern. The incident solar-radiation profile was examined and its effect on crop yield determined. The study involved four different species of shrubs (Leucaena leucocephala (Lam) de Wit, Gliricidia sepium (Jacq.) Walp, Alchornea cordifolia, and Acioa barterii), planted at two row spacings (2 and 4 m) and two fertilizer rates (F1=45-20-20 and F2=90-40-40 kg of N-P-K ha−1) applied to the maize crop only. The hedgerows were periodically pruned, and the prunings added as mulch to the respective plots. The control plots were cropped without hedgerows. There was partial shading of the crops by the hedgerows despite periodic pruning of the shrubs. Incident radiation measured at the height of the leaves subtending the ear in maize, and just above the canopy in cowpea, decreased exponentially as a function of an index defined by the ratio of the relative height of the shrubs above the respective height of measurement in the crops (Hs−Hc) to the distance (D) between the hedgerow and the adjacent crop row. A higher degree of shading associated with the faster growing species (Leucaena, Gliricidia) and/or closer inter-hedgerow spacing resulted in corresponding decreases in crop yield. Larger amounts of hedgerow biomass production (> 5 t ha−1 dry weight) were found to be associated with significant decreases in crop yields owing to increased hedgerow shading particularly with Leucaena. Hedgerows and the organic residue mulch from the prunings contributed to an overall improvement in soil moisture retention.